Is high-tech zone a policy trap or a growth drive? Insights from the perspective of urban land use efficiency. (June 2020) - Lu, Xinhai; Chen, Danling; Kuang, Bing; Zhang, Chaozheng; Cheng, Chen
Highlights: How high-tech zones (NHTZs) policies affect urban land use efficiency (ULUE) is investigated. Double-difference method was used to study net impacts of NHTZs policies on ULUE. NHTZs policies have significantly increased and stimulated ULUE. The effect of NHTZs policies on ULUE showed a remarkable regional difference. The time cumulative effect of NHTZs had the highest positive impact on ULUE. Abstract: The increasing number of national high-tech zones (NHTZs) in China has triggered significant changes in land use. Several researchers argued that urban land use efficiency (ULUE) may decrease, due to the so-called "development zone fever". However, using a super-efficient Slacks-based measure (SBM) model and the Double-difference model, we found that, from the perspectives of scale, factor accumulation, and agglomeration effects, NHTZs policies had a positive impact on ULUE in 285 Chinese cities in the period 2003–2016. In addition, the net effects of NHTZs policies on ULUE were 1.13 % in eastern cities, 0.38 % in central cities, and 0.19 % in western cities. Furthermore, different regions experienced differential impacts from economic development, urbanization level, industrial structure, population, foreign direct investment (FDI), and land marketization. A further empirical test found that the cumulative impacts of NHTZs policies on ULUE are related to both quantity and time. Among these, NHTZs growth time had the highest positive impact on ULUE. This study provides empirical justification for the establishment of NHTZs in China.